2019
DOI: 10.3390/ijerph16030492
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Obesity among Malaysian University Students: A Combination Study with the Application of Bayesian Structural Equation Modelling and Pearson Correlation

Abstract: In obesity modelling studies, researchers have been seeking to identify the effective indicators of obesity by using appropriate statistical or mathematical techniques. The main objective of the present study is addressed in three stages. First, a new framework for modelling obesity in university students is introduced. The second stage involves data analysis based on Bayesian Structural Equation Modelling (BSEM) for estimating the Body Mass Index (BMI) (representative of the obesity level) of students at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
4
22
0
Order By: Relevance
“…Dietary risk scores of students were largely consistent across all countries with few differences observed. These findings are consistent with the current literature [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Students from the USA reported the highest absolute dietary risk score, which is consistent with the higher prevalence of overweight and obesity among American students, and higher BMI compared to students in the other countries studied [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Dietary risk scores of students were largely consistent across all countries with few differences observed. These findings are consistent with the current literature [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Students from the USA reported the highest absolute dietary risk score, which is consistent with the higher prevalence of overweight and obesity among American students, and higher BMI compared to students in the other countries studied [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with the current literature [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Students from the USA reported the highest absolute dietary risk score, which is consistent with the higher prevalence of overweight and obesity among American students, and higher BMI compared to students in the other countries studied [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Even though the prevalence of overweight and obesity was higher among USA students, previous work reported that the majority of students from the USA and other countries did not meet the daily recommended servings of fruit and vegetable intake [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Discussionsupporting
confidence: 94%
“…The elements of lifestyle are one of the leading research variables that are included in the obesity modelling. This was present in some of the previous studies related to children [40] and youth [41]. Those studies showed that the links between the demographics had allowed the BMI to be examined through lifestyle, food intake, and mental health.…”
Section: Aim Of the Study And Research Frameworkmentioning
confidence: 83%
“…This latent variable is been used for the first time to measure the impact of this latent variable on postpartum obesity modeling. Mental health has been used in previous studies but in a different context [41,62]. Yet, there is a lack of studies in postpartum obesity modeling that used mental health as a latent variable.…”
Section: Mental Health (Third Mediator)mentioning
confidence: 99%
“…(7)(8)(9) . Nevertheless, to the best of our knowledge, very few studies (11) have assessed the aetiology of obesity in university student populations from a broad perspective (that includes different determinants and their possible interactions), even though this population is particularly vulnerable to inadequate lifestyles, which have consequences on their health status (12,13) .…”
mentioning
confidence: 99%